2005
DOI: 10.4049/jimmunol.175.11.7209
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Immunodominant HY H2-Dk Epitope and Evaluation of the Role of Direct and Indirect Antigen Presentation in HY Responses

Abstract: Minor histocompatibility Ags derive from self-proteins and provoke allograft rejection and graft-vs-host disease in MHC-matched donor-recipient combinations. In this study, we define the HYDk epitope of the HY minor histocompatibility Ag as the 8mer peptide RRLRKTLL derived from the Smcy gene. Using HY tetramers, the response to this peptide was found to be immunodominant among the four characterized MHC class I-restricted HY epitopes (HYDkSmcy (defined here), HYKkSmcy, HYDbUty, and HYDbSmcy). Indirect present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…In cytotoxicity assays T cells were incubated with IFN-γ-treated ECs derived from WT and CD31-deficient female mice (H-2 b background) pulsed with the HY-derived Uty peptide (52). As a control non-peptide-pulsed ECs were used.…”
Section: Methodsmentioning
confidence: 99%
“…In cytotoxicity assays T cells were incubated with IFN-γ-treated ECs derived from WT and CD31-deficient female mice (H-2 b background) pulsed with the HY-derived Uty peptide (52). As a control non-peptide-pulsed ECs were used.…”
Section: Methodsmentioning
confidence: 99%
“…They have identified HY antigenic peptides encoded by the Smcy gene, including the dominant peptide RRLRKTLL presented by the H2-D k class I molecule and the peptide TENSGKDI presented by H2-K k (19,20). We observed that female CBA mice produce CTL against male target cells expressing both peptides after grafting with syngeneic male, but not female, skin.…”
Section: Resultsmentioning
confidence: 83%
“…For individual minor histocompatibility Ags, relative tissue susceptibility is likely to differ and be controlled by multiple factors including epitope density and properties of the T cell repertoire. For example, although the H2 krestricted CD8 T cell response to HY is immunodominant over the H2 b response (19) and both reject hemopoietic cell grafts, H2 brestricted CD8 T cells are more effective at eliciting skin graft rejection. The most attractive targets for promoting the graft-vsleukemia effect without GvH disease are, however, those minor histocompatibility Ags whose expression is restricted to hemopoietic lineages (42).…”
Section: Effector Functionmentioning
confidence: 99%
“…To explore the mechanism(s) limiting the response, we first characterized the immunodominant HYD k -specific CD8 T response (19) in the H2 k strains CBA and B10.BR. Females were immunized with male spleen cells and peripheral blood analyzed using HYD k Smcy tetramer.…”
Section: Defective Cd4mentioning
confidence: 99%
See 1 more Smart Citation